تحليل الدلالة النفسية والاجتماعية للألفاظ والتراكيب في قصيدة العينية للشاعر أبي مسلم البهلاني /Analyzing the psychological and social meanings in the sample poem (Al-‘Ainiyyah) by the Omani poet Abu Muslim Al-Bahlani - Suad Saeed Ali Alduagishi (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2023)
ملخص البحث: هدف هذا البحث إلى تحليل الدلالة النفسية والاجتماعية في القصيدة العينية )أفيقوا بني القرآن) للشاعر العماني أبي مسلم البهلاني، وهي قصيدة قصد منها الشاعر استنهاض أمته الإسلامية لمواجهة من يتربصون بالإسلام وأهله ويدعوهم فيها إلى مؤازرة دعاة الحق، وقد استعملت في البحث المنهج الوصفي التحليلي، وخلص البحث بنتائج أهمها: مدى عناية علماء اللغة بالدلالات التي تحملها الألفاظ المستعملة في اللغة لما لها من دور في الكشف عن المعاني التي يريد المتكلم إيصالها إلى المتلقي وبيان مقصوده منها، وقد اتضح من التحليل النفسي وجود الدلالات النفسية المباشرة وغير المباشرة في القصيدة التي تشي عن نفسية الشاعر الغيورة على دينها المتحمسة لنصرته ونصرة أصحاب الحق، فتبين حسن اختيار الشاعر لألفاظ القصيدة وقافيتها الذي تناسب مع نفسيته في استنهاض أمته. ومن التحليل الاجتماعي تكشفت ثقافة الشاعر الدينية المتأثرة ببيئته الاجتماعية؛ وذلك من تحليل كلمتي الجهاد والعقاب المناسبتين لغرض القصيدة، وكذلك من توضيح بعض العناصر الاجتماعية في القصيدة ومن استعمال الشاعر للتشبيه والكناية والاستعارة. الكلمات المفتاحية: تحليل، الدلالة النفسية، الدلالة الاجتماعية، قصيدة العينية، الشاعر أبو مسلم البهلاني. Abstract This research aims to analyze the psychological and social meanings in the sample poem (Wake Up, Children of the Quran) by the Omani poet Abu Muslim Al-Bahlani. It is a poem composed to arouse Muslims to face those who are hostile to Islam and Muslims, and call them to support the supporters of truth. Descriptive and analytical methods are used in the research. Among the findings of the study are: Linguists pay attention to the connotations brought by the words used in the language, because of their role in revealing the meaning that the speaker wants to convey to the receiver, and explaining the meaning by them. Psychological analysis found that there are direct and indirect psychological connotations in the poem that reveals the psychology of the poet, who has a high spirit in preserving religion and supporting the truth. The study also found that the choice of words and rhymes of the poem fit his soul that wants to move his nation. Social analysis reveals that the poet’s religious culture is influenced by his social environment. This is understood from the analysis of the words jihad and punishment suitable for the purpose of the poem, as well as explaining some social elements in the poem and from the poet’s use of simile, metonymy, and metaphor. Keywords: analysis, Psychological importance, Social interest, Al-Ainya poetry, Poet Abu Muslim Al-Bahlani. Abstrak Penyelidikan ini bertujuan menganalisis makna-nakna psikologi dan sosial dalam puisi sampel (Bangun, Anak-anak Al-Quran) oleh penyair Oman Abu Muslim Al-Bahlani. Ia adalah puisi yang digubah bagi membangkitkan umat Islam untuk menghadapi mereka yang memusuhi Islam dan umat Islam,dan menyeru mereka untuk menyokong penyokong kebenaran. Kaedah deskriptif dan analisis digunakan dalam penyelidikan. Antara dapatan kajian adalah: Ahli bahasa memberi perhatian kepada konotasi yang dibawa oleh perkataan yang digunakan dalam bahasa, kerana peranan mereka dalam mendedahkan makna yang ingin disampaikan oleh penutur kepada penerima, dan menjelaskan maksudnya oleh mereka. Analisis psikologi mendapati bahawa terdapat konotasi psikologi secara langsung dan tidak langsung dalam puisi yang menyingkap psikologi penyair, yang mempunyai semangat tinggi dalam memelihara agama dan pendokong kebenaran. Kajian juga mendapati bahawa pemilihan kata dan rima puisi sesuai dengan jiwanya yang mahu menggerakkan bangsanya. Analisis sosial menyingkap bahwa budaya keagamaan penyair dipengaruhi oleh persekitaran sosialnya. Ini difahami dari analisa terhadap perkataan jihad dan hukuman yang sesuai untuk tujuan puisi, serta menjelaskan beberapa unsur sosial dalam puisi dan daripada penggunaan simile, metonimi, dan metafora penyair. Kata kunci: analisis, kepentingan psikologi, kepentingan sosial, puisi Al-Ainya, penyair Abu Muslim Al-Bahlani.